Specialised predation by great tit Parus major on peacock butterflies Aglais io and small tortoiseshells Aglais urticae - Andersson, Gunnar; Brodin, Anders (Ornis Svecica, 2026)
The great tit Parus major is known for its wide range of innovative foraging behaviours, which have enabled adaptation to anthropogenic habitats such as gardens and city parks. Some of the behaviours are general and common whereas others are rare and seem to have been invented and used by single birds. Here we report on a male great tit that specialised in capturing large butterflies that were foraging in a flowering butterfly bush Buddleja davidii in northeastern Skåne, southernmost Sweden. Coming from a nearby Thuja sp. tree, the bird discretely flew to the bush just above ground level and perched at the bottom of it. It then flew straight upwards and grabbed a butterfly from beneath, flew back to perch in the Thuja, tear the wings off the butterfly and eat it. In one day, it left a pile of wings from at least 18 peacock butterflies Aglais io, four small tortoiseshells Aglais urticae and one large yellow underwing Noctua pronuba. Despite great tits being very good observational learners, no local conspecific copied this successful behaviour.